2022
DOI: 10.1182/bloodadvances.2021004970
|View full text |Cite
|
Sign up to set email alerts
|

Quality-of-life analysis of pembrolizumab vs brentuximab vedotin for relapsed/refractory classical Hodgkin lymphoma

Abstract: KEYNOTE-204 (NCT02684292) demonstrated progression-free survival (PFS) advantage for pembrolizumab over brentuximab vedotin (BV) in patients who had relapsed or refractory classical Hodgkin lymphoma (R/R cHL) following, or who were ineligible for, autologous stem cell transplantation (ASCT). Health-related quality of life (HRQoL), measured by patient-reported outcomes (PROs) from KEYNOTE-204, are reported from patients who received ≥1 dose of study treatment and completed ≥1 PRO assessment. QLQ-C30 and EuroQoL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…A preliminary analysis of patient-reported outcomes shows improved global QoL score after NIVAHL treatment, in line with anti–PD-1-based treatment in relapsed HL. 11-13 Although preliminary, this indirectly compares favorably with global QoL after conventional chemotherapy in early-stage unfavorable HL. 14…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A preliminary analysis of patient-reported outcomes shows improved global QoL score after NIVAHL treatment, in line with anti–PD-1-based treatment in relapsed HL. 11-13 Although preliminary, this indirectly compares favorably with global QoL after conventional chemotherapy in early-stage unfavorable HL. 14…”
Section: Discussionmentioning
confidence: 88%
“…A preliminary analysis of patient-reported outcomes shows improved global QoL score after NIVAHL treatment, in line with anti-PD-1-based treatment in relapsed HL. [11][12][13] Although preliminary, this indirectly compares favorably with global QoL after conventional chemotherapy in early-stage unfavorable HL. 14 Ann Arbor stage is defined as follows: stage I, nodal involvement in a single region or a single localized extranodal involvement; stage II, nodal involvement and/or localized extranodal involvements in two or more regions on one side of the diaphragm; stage III, nodal involvement and/or localized extranodal involvements on both sides of the diaphragm; stage IV, disseminated involvement of one or more extralymphatic organs with or without involvement of lymph nodes; stages I-IV are given the suffix B if one or more of the following general symptoms are present and the suffix A if the following symptoms are absent: fever more than 38°C that cannot be attributed to anything else, night sweats (with change of bed linen) that cannot be attributed to anything else, and loss of weight of more than 10% of body weight within 6 months that cannot be attributed to anything else.…”
Section: Discussionmentioning
confidence: 89%
“…At this time, there are no large-scale, published studies describing the safety and efficacy of pembrolizumab in pediatric and adolescent patients with HL who received the drug for R/R disease. However, Zinzani et al [ 181 ] recently reported that, compared to BV, pembrolizumab demonstrated overall improvements in patient-reported outcomes of health-related quality-of-life measures in the KEYNOTE-204 study. Although the study’s complete results have not been published yet, the findings are compelling enough to make pembrolizumab a preferred choice for R/R cHL patients who are either ineligible for or have experienced a relapse after ASCT [ 155 , 181 ].…”
Section: Novel Therapies For R/r Hlmentioning
confidence: 99%
“…In the pivotal phase 2 trial of single agent BV, patients achieving CR (34%) had durable responses, with 38% of these patients remaining in remission for over 5 years [ 24 ]. Compared to single agent BV, pembrolizumab demonstrated a higher ORR (65.6% vs. 54.2%), a longer median PFS (13.2 vs. 8.3 months), and improved health-related quality of life in the randomized phase 3 KEYNOTE-204 trial, which was enriched for transplant-ineligible patients (63%) [ 70 , 71 ]. For patients responding to PD-1 inhibitors, we continue treatment for up to 1–2 years, depending on the depth of response.…”
Section: Management Of Transplant Ineligible Patientsmentioning
confidence: 99%